Not a whim, just esteem. Esteem in the Questionnaire Responses of Lublin Students - Gierczak, Sylwia Katarzyna (Vilnius University Open Series, 2021)
This paper aims to present and discuss the results of a survey study concerning the notion of SZACUNEK (“esteem”). The survey was conducted in a group of students from Lublin universities: Maria Curie-Skłodowska University, John Paul II Catholic University of Lublin, University of Life Sciences in Lublin, Medical University of Lublin and Lublin University of Technology. The participants of the study included male and female students pursuing both STEM and liberal arts degrees.The present paper is situated within the research on the language of values, which has its framework in the context of the five-volume Leksykon aksjologiczny Słowian i ich sąsiadów (“Axiological Lexicon of Slavs and Their Neighbours”) published under the scholarly and editorial direction of Jerzy Bartmiński as part of the international conference EUROJOS. The analyses discussed by the author were carried out in accordance with the methodological approach adopted in the report Język – wartości – polityka. Zmiany rozumienia nazw wartości w okresie transformacji ustrojowej w Polsce (“Language, Values, Politics. Evolution of the Understanding of Names of Values during the System Transformation in Poland”) published under the direction of Jerzy Bartmiński.The survey study made use of the Axiological Dictionary Questionnaire. All respondents were obligatorily asked the following question: “What – in your view – constitutes the essence of esteem?”. The analysis and discussion of questionnaire results was based on 100 responses (N) and 142 “mini-responses” (W). This allowed to distinguish 28 descriptors (D), 15 of which had only single occurrences. Descriptor characteristics (along with the corresponding phrases) were ordered according to the number of occurrences and assigned to appropriate aspects. Six aspects characteristic for the students’ view of ESTEEM were distinguished.
Keywords: semantics; ethnolinguistics; linguistic axiology; esteem; questionnaire